The pathogenetic role of vitamin D and vitamin D-binding protein in the development of urinary tract infection in children - Lezhenko, G. O.; Abaturov, O. Ye.; Zakharchenko, N. A.; Леженко, Геннадій Олександрович; Абатуров, О. Є; Захарченко, Наталія Анатоліївна (My University, 2022)
Abstract. The aim of the research. To study the content of 1,25(OH)2D3 and DBP in the blood serum of children with urinary tract infections, taking into account the clinical form of the disease, and to establish their pathogenetic role in the development of urinary tract infections. Materials and methods. The study groups consisted of 84 children (mean age - 10 ± 1.3 years). The main group was divided into subgroups: the first subgroup - 17 children with acute pyelonephritis, the second subgroup - 21 patients with chronic pyelonephritis, the third subgroup - 16 patients with acute cystitis, the fourth subgroup - 10 patients with unspecified urinary tract infections. The control group consisted of 20 relatively healthy children. The content of 1,25(OH)2D3 and DBP was investigated by immunoenzymatic analysis. Results. It was found that the development of the inflammatory process in the urinary tract was accompanied by a statistically significant (p<0.01) decrease in the level of 1,25(OH)2D3 in the blood serum of the children of the main group, compared to the children of the control group. The level of 1,25(OH)2D3 in patients of all subgroups was significantly lower than that of the control group (p<0.01), but there was no statistical difference between them. The level of DBP in the blood serum of the children of the main group was statistically significantly (p<0.05) increased, compared to the children of the control group, but we did not find a statistically significant difference between the subgroups studied. Conclusions. The development of an acute inflammatory process in the urinary tract in children occurs against the background of a statistically significant decrease in the level of 1,25(OH)2D3 in blood serum in combination with high levels of vitamin D-binding protein. This serves as a pathogenetic basis for the need to develop therapeutic and prophylactic schemes for prescribing vitamin D to children with urinary tract infections. Мета роботи. Дослідити вміст 1,25(OH)2 D3 та вітамін D-зв’язуючого білка (DBP) у сироватці крові дітей з інфекціями сечовидільної системи залежно вiд клінічної форми захворювання та встановити їх патогенетичну роль у розвитку інфекції сечовивідних шляхів. Матеріали та методи. Групи дослідження становили 84 дитини (середній вік — 10,0 ± 1,3 року). Основну групу розділили на підгрупи: 1-ша — 17 дітей, хворих на гострий пієлонефрит, 2-га — 21 пацієнт із хронічним пієлонефритом, 3-тя — 16 дітей, хворих на гострий цистит, 4-та — 10 пацієнтів із неуточненими інфекціями сечовидільної системи. Контрольну групу становили 20 умовно здорових дітей. Досліджували вміст 1,25(OH)2 D3 та DBP методом імуноферментного аналізу. Результати. Встановлено, що розвиток запального процесу в сечовивідних шляхах супроводжувався статистично значущим (р < 0,01) зниженням рівня 1,25(OH)2 D3 у сироватці крові дітей основної групи порівняно з контрольною. Уміст 1,25(OH)2 D3 у пацієнтів усіх підгруп був достовірно нижчим за показники контрольної групи (р < 0,01), проте без статистичної різниці. Рівень DBP у сироватці крові дітей основної групи був статистично значуще (р < 0,05) підвищеним порівняно з контрольною, але статистично значущої різниці між підгрупами, що досліджувалися, ми не виявили. Висновки. Розвиток гострого запального процесу в сечовивідних шляхах у дітей відбувається на тлі статистично значущого зниження рівня 1,25(OH)2 D3 у сироватці крові в поєднанні з високими рівнями вітамін D-зв’язуючого білка. Це виступає патогенетичним підґрунтям необхідності розробки терапевтичних і профілактичних схем призначення вітаміну D дітям з інфекціями сечовидільної системи.
Патогенетична роль вітаміну D та вітамін D-зв’язуючого білка в розвитку інфекції сечовивідних шляхів у дітей
Keywords: children; urinary tract infection; vitamin D; vitamin D-binding protein; діти; інфекція сечовивідних шляхів; вітамін D; вітамін D-зв’язуючий білок